The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1002/jcu.20175
|View full text |Cite
|
Sign up to set email alerts
|

Power Doppler assessment of overall disease activity in patients with rheumatoid arthritis

Abstract: PDUS appears to be a reliable method for assessing inflammatory activity in rheumatoid synovium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 24 publications
1
15
0
3
Order By: Relevance
“…This study also found a significant inverse correlation between RI and fl ow signal intensity, which others and we have previously reported. [16][17][18][19][20] Taken together, the results of the present study suggest that the degree of synovial effusion had a stronger association with the increased grades of fl ow signals which have higher perfusion (lower RI values) and are located in the superfi cial layer of the pannus, whereas pannus thickness had a stronger association with the larger vessels which have lower perfusion (higher RI values) and are located in the deep layer of the pannus.…”
Section: Color-fl Ow Signals and Rimentioning
confidence: 49%
“…This study also found a significant inverse correlation between RI and fl ow signal intensity, which others and we have previously reported. [16][17][18][19][20] Taken together, the results of the present study suggest that the degree of synovial effusion had a stronger association with the increased grades of fl ow signals which have higher perfusion (lower RI values) and are located in the superfi cial layer of the pannus, whereas pannus thickness had a stronger association with the larger vessels which have lower perfusion (higher RI values) and are located in the deep layer of the pannus.…”
Section: Color-fl Ow Signals and Rimentioning
confidence: 49%
“…2). Joint destruction is closely associated with increased vascularization and flow pattern (13,14). Demonstration of this vascularization during the early period of the disease can lead to an early diagnosis of RA and may lead to effective treatment before erosions and bony destruction occur.…”
Section: Rheumatoid Arthritismentioning
confidence: 99%
“…tocutaneo e l'aponeurosi palmare (3). In più con l'avvento del power Doppler l'ecografia si è reso uno strumento indispensabile per la valutazione non solo quantitativa ma anche qualitativa della sinovite fornendo una lettura immediata riguardo il suo stato di vascolarizzazione, indice di attività della malattia (4,5). Si può facilmente notare la notevole quantità di informazioni che possono essere ottenute con questa metodica.…”
Section: L'unclassified